Fluid dynamics of life: exploring the physiology and importance of water in the critical illness - Robayo-Amortegui, Henry; Quintero-Altare, Alejandro; Florez-Navas, Catalina; Serna-Palacios, Isacio; Súarez-Saavedra, Andrea; Buitrago-Bernal, Ricardo; Casallas-Barrera, Julian Orlando (Frontiers in Medicine, 2024)
Water acknowledged as a vital component for life and the universal solvent, is crucial for diverse physiological processes in the human body. While essential for survival, the human body lacks the capacity to produce water, emphasizing the need for regular ingestion to maintain a homeostatic environment. The human body, predominantly composed of water, exhibits remarkable biochemical properties, playing a pivotal role in processes such as protein transport, thermoregulation, the cell cycle, and acid–base balance. This review delves into comprehending the molecular characteristics of water and its interactions within the human body. The article offers valuable insights into the intricate relationship between water and critical illness. Through a comprehensive exploration, it seeks to enhance our understanding of water’s pivotal role in sustaining overall human health.